Photoelectrochemical Behavior of Heterostructure Based on Doping Effect: BiVO4/BiV1−xTixO4 System - Anna A. Murashkina; Tair V. Bakiev; Aida V. Rudakova; Alexei V. Emeline; Detlef W. Bahnemann (ChemElectroChem)
In this study, a set of Ti‐doped BiVO4 photoelectrodes with Ti content varying in the range from 0 to 10 at% is synthesized. All synthesized samples are characterized by XRD, Raman spectroscopy, XPS, UPS, and Kelvin probe methods confirming the formation of the target materials. UPS and Kelvin probe results demonstrate an alteration of the Fermi level position in Ti‐doped BiVO4 depending on the dopant concentration. Consequently, heterostructured electrodes based on pristine and Ti(10 at%)‐doped BiVO4 are formed providing the maximum gradient between the Fermi level position of the heterostructure's components. Photoelectrochemical studies demonstrate that Ti doping significantly affects the behavior of electrodes switching them from anodic to cathodic regime. Moreover, either anodic or cathodic behavior of heterostructured electrodes depends on the spatial layer‐by‐layer construction of the electrodes, that is, on the direction of the Fermi level gradient between heterostructure's components. Photoelectrochemical experiments performed with a tandem photoelectrochemical cell with two photoactive electrodes based on pristine and Ti(10 at%)‐doped BiVO4 demonstrate that stable photocurrent in the system is generated only when both photoelectrodes are photoexcited that confirms that the pre‐existing Fermi level gradient between the two electrodes induces the driving force for photoelectrochemical activity in the tandem cell.